2013
DOI: 10.1097/ico.0b013e3182685c8e
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Cooling Effect of Insulated Containers for the Shipment of Corneal Tissue and Recommendations for Transport

Abstract: All of the container sizes successfully maintained proper cooling when packed with the appropriate grams of wet ice for the needed time interval. This study validates current practice for the shipment of corneal tissue in inexpensive, generic containers that can maintain effective cooling for the duration required for local, national, and international shipment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Studies have found that an effective concentration of a single cryopreservative is toxic to CECs, yet the mixture of preservatives or the addition of preservatives at low temperatures seems to reduce toxicity [120]. As a means of corneal preservation, further study is warranted to investigate whether vitrification would achieve good results.…”
Section: Effect Of Corneal Cryopreservationmentioning
confidence: 99%
“…Studies have found that an effective concentration of a single cryopreservative is toxic to CECs, yet the mixture of preservatives or the addition of preservatives at low temperatures seems to reduce toxicity [120]. As a means of corneal preservation, further study is warranted to investigate whether vitrification would achieve good results.…”
Section: Effect Of Corneal Cryopreservationmentioning
confidence: 99%
“…The transportation of tissues depends on the nature of the samples, whether the samples are preserved or live, but also depends on the shipment method, whether this is by air or road transportation [6]. Several published studies have reported the successful transportation of tissues at cooled or frozen conditions using commercially available containers [8,9]. Specifically, in 2013 a study using cornea and blood revealed the maintenance of cooling temperatures during organ shipment [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several published studies have reported the successful transportation of tissues at cooled or frozen conditions using commercially available containers [8,9]. Specifically, in 2013 a study using cornea and blood revealed the maintenance of cooling temperatures during organ shipment [9]. Another study demonstrated the successful shipment of femoral head tissue and Achilles tendon at -40˚C for at least 48 hours indicating that the safety and quality of human tissue could be maintained during transportation at during shipment [8].…”
Section: Introductionmentioning
confidence: 99%
“…In many developing countries, cultural and religious concerns limit organ donations [ 4 , 5 ]. Furthermore, healthcare and financial restrictions can be a major barrier: for example, a donor cornea from an eye bank in the United States can cost about $3,000 due to the need for microbial testing, administration, and transport alone [ 6 ]. Thus, the lack of human donor tissue at a reasonable cost is one of the largest barriers to reducing blindness through either standard PK or KPro implantation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%